Estado, democracia e gênero humano: a crítica de 1843 e a fundação do pensamento marxiano - Marco Aurélio Palú (2019)
The present research aims to investigate the manuscripts of the German philosopherKarl Marx (1818-1883) of 1843, known as Hegel's Critique of Philosophy of Law,written between May and August of that year. The text in question encompassesreflections about the state, democracy and human gener- ation, which we can refer to asthe categories that make up the transition period to Marx's adult thought. These themesare worked out by the German thinker in critical dialogue with Hegel's Principles ofPhilosophy of Right, which drew a major debate in Prussia in the 1840s. The readingand immanent analysis of the manuscript reveals that it was through ontologicalcriticism of the Hegelian reflection on the State, developed by means of glosses to thetext, which Marx transposed to his own thought. It is emphasized that it was onlythrough this critical procedure that Marx's thought reached its adult stage, that is, theproper level in which his reflections and propositions reached a first maturity, to which,we emphasize, was achieved through the categories of state, democracy and humangener- ation. Thus, it is justified to return the lines of the Marxian manuscript in theexamination of the original status of the author's thought, understood here as anontological statute. The clarification of the aporias, gaps, inflections, and otherlineaments of the text shows that they were absent or still problematically present inMarxist philosophy and Marxism, and, in short, in studies that dealt with the origins ofMarxian thought. Finally, it is understood that such itinerary of dialogue with thistradition is fundamental in the interest location of our research.